SAFEGUARD RE-INVESTIGATION BY MADAGASCAR GOVERNMENT ON PASTA PRODUCTS FROM INDONESIA BASED ON GATT/WTO FRAMEWORK - Tirza Gracia Shekinah Hutagaol; FX. Joko Priyono; Nanik Trihastuti (Fakultas Hukum, Universitas Diponegoro, 2021)
Due to the increase of import in the last 4 years, Madagascar investigated imported pastain October 2018, terminated it on July 10, 2019, and reinvestigated it on July 18, 2019. They were followed with Provisional Safeguard Measures(PSM). This study aimed to know whether Madagascar had been fulfilling the elements of Article XIX GATT in the preliminary determination of investigation and whether a safeguard reinvestigation is in accordance with the GATT/WTO. Researchers used a juridical normative approach. The result showed that serious injuries and causal links from Article XIX GATT were undetermined in the preliminary determination. Neither the GATT nor Agreement on Safeguard (SA) were not regulating safeguard reinvestigation, so it can proceed but without PSM in the second investigation, because it violated the provisions of Article 6 SA.Madagascar shall immediately completing the elements that had not been determined and revoke the PSM in the second investigation.